Facilitating Student Outcomes by Supporting Autonomy: Implications for Practice and Policy. (October 2019) - Patall, Erika A.; Zambrano, Jeanette
All students come to the classroom with inner motivational resources that, when supported, catalyze engagement, motivation, learning, and achievement. Teachers' support for student autonomy is an essential tool for enhancing desirable student outcomes; practitioners and policy-makers can promote autonomy-supportive classroom environments. An overview of autonomy support presents core, autonomy-supportive practices: (a) providing choice opportunities, (b) providing rationales, and (c) incorporating student perspectives. Next, we address common misconceptions about autonomy support and consider why practitioners often do not adopt an autonomy-supportive approach. Finally, autonomy support might help to address broader societal challenges, with strategic implications for researchers, educators, and policy-makers.